PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MASKER MEREK SENSI DI BORMA TOSERBA CIJERAH KOTA BANDUNG - Anisa Shintiani; Desta Sulaesih; Tina Merlina (Universitas Nurtanio Bandung, 2022)
The purpose of this research is to determine the effect of Brand Image and ProductQuality on Purchase Decisions for Sensi Mask Products at BormaToserbaCijerah. Sensi mask reaches the highest selling mask products based on the data’spercentage of mask sales in BormaToserbaCijerah. This researchmethod uses a quantitative approach with multiple linear regression analysis. Thesource of this research uses primary data. The data collection uses aquestionnaire. The samplesfrom this research are about 100 consumers using purposivesampling technique. The test results are hypothesized to show that Brand Imageand Product Quality have a significant influence either partially orsimultaneously on the Purchase Decision of Sensi Mask Products. For further research, it is expected to be able to examine other variables such as price, Brand Ambassador, promotions, consumer buying interest, therefore it may be easier to obtain varied results that can influence purchasing decisions. Keywords:Brand Image, Purchase Decision, Product Quality